MODEL MITIGASI BENCANA DI WILAYAH PESISIR DENGAN PEMBERDAYAAN MASYARAKAT - Haryani Haryani (TATALOKA, 2012)
More than 110 millions Indonesian peoples lives in coastal areas and small islands which is highly affected by natural disaster such as volcanic and tectonic earthquake(Dahuri,R.2001). Around 400,000 from total population of 850,000 peoples in Padang, lives in the coastal area(Rencana Strategis Wilayah Pesisir dan Laut Kota Padang, 2007). Based on the above facts, this research try to create mitigation model in Padang City’s coastal areas through community participations against tsunami, coastal abrasion, earthquake and high/low tide with case study in Kelurahan Pasie Nan Tigo, Kecamatan Koto Tangah. Active participations by the community  to create disaster mitigation model in coastal area are needed because the community’s knowledge of their day to day problems related to natural disaster could pro-actively minimize the impact of the disaster which probably occur in their living area